ANALYSIS OF INTEGRATION OF DISASTER EDUCATION IN SCIENCE SUBJECT ON THE TOPIC OF WAVES AND DISASTERS - Mila Dewi Laraswati; Mudmainah Vitasari; Prasetyaningsih Prasetyaningsih (Jurnal Pembelajaran Sains, 2020)
Formal education is an effective means of providing education related to disaster risk reduction by integrating disaster material into the curriculum. One of the subjects that can be integrated with disaster material is science subjects. In the learning process, science is taught in an integrated manner which means connecting science with various fields of study manifested by a learning theme. This study aims to analyze the integration of disaster education in the 2013 curriculum in the Natural Science subject with the theme of Waves and Disasters in junior high schools. This research uses descriptive qualitative method. The data collection technique in this research is literature study. The results showed that: The theme of learning Waves and Disasters is a theme that is packaged with a webbed integrated model that can teach disaster education in science subjects. Basic competencies (KD) that can teach the theme are KD 3.10 regarding the layers of the earth and disasters and KD 4.10 regarding communicating disaster risk reduction efforts in grades VII and KD 3.11 regarding vibrations, waves, sound and KD 4.11 regarding presenting experimental results of vibrations, waves and sounds in grades VIII.